Analysis of the Main Characters in Film Titanic by James Cameron - Imakulata Suryani Danda; Ni Nyoman Deni Ariyaningsih (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2024)
This study is mainly focus on to find out the types of characters and the characterizations of the main character in the film entitle “Titanic” by James Cameron. The study used two theories. The first theory is developed by Kenney ( 1998) that is used in analyzing the  types of main character and the second theory from  Wellek and Warren (1976) which is used  in analyzing the characterization of the main character. The data were qualitatively analyzed and  presented descriptively based on the theories adopted.  Protagonist character was found as the finding result of  the study the type of the character classified as major and dynamic character. In showing  the type of the character and characterization of main character,the analysis used picture or scenes and the dialogue from the film. There are three aspects of characterization  of all main characters that were found. Those are physiological, psychological and sociological aspects.